Eksistensi Dayah Darul Muta’allimin Tanah Merah dalam Meningkatkan Akhlak Masyarakat Aceh Singkil - Hambalisyah Hambalisyah; Mukhsin Nyak Umar; Yusra Jamali (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
The purpose of this article is to review: (1) The existence carried out by Dayah with the local community in the Aceh Singkil area; (2) Dayah's efforts in improving morals towards the community. This research uses descriptive qualitative research methods with data collection techniques through interviews, observations and documents. Data analysis techniques use: data reduction, data display, and conclusions or verification. The findings of this study are as follows: First, Dayah Darul Muta'allimin as a non-formal religious education institution has a contribution as a forum for human resource development in the religious field. Second, Dayah Darul Muta'allimin Tanah Merah's efforts in improving the morals of the Aceh Singkil community, through various activities such as holding lectures, intensive Islamic studies every month, holding regular recitation programs once a week twice, providing opportunities to study and recite the Koran at dayah, providing guidance in reading and writing the Koran to the community. Third, the supporting factors in the implementation of educational programs are: the influence of the Founder, the existence of social interaction and good cooperation between the dayah and the community and alumni, the existence of learning places and teaching staff, the realization of the people's economy. While the inhibiting factors in the implementation of local community religious education programs, namely: time that clashes with other activities, busyness during the day with their work, and lack of participation from the youth.